(untitled) (Lantanida Journal, 2017)
Interest is the tendency of a person to carry out the deed, as the interest to learn something in terms of reading, writing, or discussing. In a situation of effective learning takes place when the interest and attention of learners in learning. Hence the interest of learners very big influence in learning, because with the interest of learners will be working on something that interested him. So for the success of the study was affected by something which is in self-learners, and something that comes from outside the learner, such as teachers. Since the internal process is not immediate action, then a faculty member should be able to direct the external process such that it can affect the internal processes within learners. The influence of interest students in learning has a positive influence to the achievement of learning a subject. The higher the interest of students in learning a subject, the higher the learning outcomes achieved a subject. Conversely, the lower the interest students in learning a subject, then the lower the learning outcomes of a course that achieves.